Cosmic Noise Absorption During Solar Proton Events in WACCM‐D and Riometer Observations. Issue 2 (13th February 2019) - Heino, Erkka; Verronen, Pekka T.; Kero, Antti; Kalakoski, Niilo; Partamies, Noora
Abstract: Solar proton events (SPEs) cause large‐scale ionization in the middle atmosphere leading to ozone loss and changes in the energy budget of the middle atmosphere. The accurate implementation of SPEs and other particle ionization sources in climate models is necessary to understand the role of energetic particle precipitation in climate variability. We use riometer observations from 16 riometer stations and the Whole Atmosphere Community Climate Model with added D region ion chemistry (WACCM‐D) to study the spatial and temporal extent of cosmic noise absorption (CNA) during 62 SPEs from 2000 to 2005. We also present a correction method for the nonlinear response of observed CNA during intense absorption events. We find that WACCM‐D can reproduce the observed CNA well with some need for future improvement and testing of the used energetic particle precipitation forcing. The average absolute difference between the model and the observations is found to be less than 0.5 dB poleward of about 66° geomagnetic latitude, and increasing with decreasing latitude to about 1 dB equatorward of about 66° geomagnetic latitude. The differences are largest during twilight conditions where the modeled changes in CNA are more abrupt compared to observations. An overestimation of about 1° to 3° geomagnetic latitude in the extent of the CNA is observed due to the fixed proton cutoff latitude in the model. An unexplained underestimation of CNA by the model during sunlit conditions is observed at stations within the polar cap during 18 of the studied events. Key Points: CNA during 62 SPEs was studied with WACCM‐D and riometer observations CNA is modeled well on average and in individual events with a nonlinearity correction for high levels of CNA The fixed proton cutoff latitude in WACCM‐D at 60 degrees leads to overestimation of the extent of the CNA, especially in small to moderate SPEs